The Effect of the Emotional Demonstration Method of Mealing Schedule on the Knowledge of Mothers to Children in Posyandu V Mulyorejo Surabaya - Nurvitriana, Nidya Comdeca; Andarwulan, Setiana (Basic and Applied Nursing Research Journal, 2021)
Background of research on mother's knowledge of toddlers in providing feeding schedules, especially snacks. Giving snacks that are not right on schedule will have an influence on the growth and development of infants. Through the Emotional Demontration method, eating schedule for snacking can be controlled. Emotional Demonstration is the provision of education not only through lectures but also through games so that the key messages conveyed can be remembered by mothers of toddlers in Posyandu V Mulyorejo Surabaya. The Emo Demo method is one solution to reduce the stunting rate. In 2017 the stunting rate in Indonesia reached 22.2%. Based on the results of the survey conducted through interviews with nutritionists, it was explained that there were 16 stunting toddlers in Posyandu V Surabaya. Quantitative Research Methodology, a quasi-experimental research design method with one group pretest posttest approach. The population in this study were all mothers of children under five in Posyandu V Mulyorejo Surabaya as many as 36 people, samples as many as 36 mothers of toddlers. With a total sampling technique. Analyze data with Paired T-test. The results showed the mean value of the pre test was 6.06, the mean value after the post test reached 8.16. While the significance value of p value = 0,000 with α = 0.05 through the Paired T-test. The conclusion is that there are differences in the knowledge of pre and post test among mothers of children under five in Posyandu V Mulyorejo Surabaya, p value = 0,000 with α = 0.05. Suggestions for health workers to continue to make improvements in practicing emotional demonstration to participants because it is very useful in increasing knowledge to prevent increased stunting rates.